PVTE system performance improvement via numerical optimization of heat sink design and fluid working conditions - Amir Azirul; Adnan Ibrahim; Nurul Syakirah Nazri; Hasila Jarimi; Muhammad Ammirrul Atiqi Mohd Zainuri; Ubaidah Syafiq (Scientific Reports)
Abstract In recent times, there has been increasing interest to address climate change by implementing renewable energy to enhance the energy sector as soon as possible. However, solar radiation turns into heat reducing the photovoltaic (PV) panel efficiency. The waste heat from PV panels can be utilized by thermoelectric (TE) to convert into electricity and enhance PV panel efficiency. In this study, the 3D CFD and thermal-electric numerical model was developed for thermal and electrical analysis of different heat sink designs and materials for a thermoelectric generator (TEG) to be used in a (PV) system. Heat sink was installed on the cold side of the Photovoltaic-Thermoelectric (PVTE) system to dissipate the heat from the PV panels, where varying flow inlets and convection coefficient parameters for dissipating the heat on the cold side of the PVTE system were investigated. The simulated TEG power generation with different heat sink designs, heat sink materials, convection coefficients (h) and flow inlets (v) were compared. The results showed that the TEG with pin fin heat sink design (H3) made from aluminium (Al) generated the highest power generations than the other designs. The results also showed the power generation significantly increases until saturation point around 2.01 m s− 1 for the flow inlet and also increases when the convection coefficient increases above 20 (W/m2) °C.